Immunohistochemical Study of p53 Expression in Colorectal Adenocarcinomas and its Clinicopathological Correlation - Chithrra, Varshaa; John, Jaison Jacob; Ganapathy, Shivashekar; Raja, Veena (Annals of Pathology and Laboratory Medicine, 2018)
Background: Colorectal carcinoma is the fourth most frequent cancer in men and the third in women worldwide. The identification of molecular markers that have a prognostic significance in colorectal carcinoma may have an impact on its treatment. This study aims to identify and evaluate the immunohistochemical expression of p53 in colorectal adenocarcinomas and to correlate its expression with various clinicopathological parameters. Methods: The present study was an observational study done in 30 surgical resection specimens received in the Department of Pathology, SRM Medical College and Research Centre, Kattankulathur, Tamil Nadu from June 2015-June 2017. Clinical history and clinicopathological parameters were obtained ,histomorphological and immunohistochemical evaluation was done and the results were correlated with clinicopathological variables. The IHC panel we used was mouse monoclonal p53 antibody (PathnSitu). Result: In our study, p53 overexpression was noted in 70% cases of colorectal adenocarcinomas. p53 overexpression was noted more in conventional adenocarcinomas (85.7%), more in left sided colonic carcinomas (71.4%), in advanced pT stage (57.1% in pT3) and also in cases with lymph node metastasis (57.1%). No statistically significant correlation of p53 with other clinicopathological variables such as age, gender, nature of specimen, tumor site, size, histological type, grade, tumor perforation, bowel wall invasion and perineural invasion were noted. Conclusion: Our study supports that p53 overexpression is an indicator of poor prognosis and may prove as an useful marker in identifying high risk patients who may benefit from adjuvant therapy in the early stage of disease.